CARDIORESPIRATORY CAPACITY (Fiep Bulletin - online, 2016)
The control of the cardiorespiratory system is a difficult task, this applies both at rest and during exercise. From this statement, we will cover in this article from concept, through the adaptations the body suffers, to the tests that assess cardiorespiratory fitness. According to the ACSM to increase cardiopulmonary resistance or VO2máx, it is necessary that the basic aerobic schedule is performed three to five times a week, with sessions twenty to sixty minutes at an intensity of 50% -85% of VO2máx (or 60% -90% of maximum heart rate). There will be greater gains in VO2max, according to the frequency, duration and intensity increase. When the goal is only to improve health, physical activity lower intensity distributed during the day seem to be enough.
Keywords: Cardiopulmonary Capacity; Heart Rate Training.